Day 3 Wed, March 28, 2018 2018
DOI: 10.2118/190469-ms
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Hydrocarbon Solvents at the Pore Scale During Hybrid Solvent-Thermal Application for Heavy-Oil Recovery

Abstract: Phase behavior of fluids at capillary conditions differs from that in bulk media. Therefore, understanding the thermodynamics of solvents in confined media is essential for modeling thermal EOR applications. The Thomson equation states that pore sizes have a control on boiling points of liquids in capillary channels. As pore spaces become smaller, boiling points become lower than normal boiling temperatures of the same liquids. The target of this paper is to inspect this phenomenon by physically measuring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Small (nano)­capillaries have a major impact on the process as boiling occurs quicker (at lower temperatures) compared to larger capillaries. , Therefore, capillary size and distribution controls the whole process, meaning further phase change and the displacement and entrapment of the gas and liquid phases. In our prior studies, vaporization temperatures of various hydrocarbons were studied using different lab-scale capillary models such as Hele–Shaw silica-glass cells, microfluidics chips, and reservoir rocks (Berea sandstone, Indiana limestone, tight sandstone, and shale). These studies qualitatively and quantitively investigated the phase behavior (boiling temperatures and pressures of hydrocarbon solvents) and showed that phase change occurs more quickly as the medium becomes tighter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small (nano)­capillaries have a major impact on the process as boiling occurs quicker (at lower temperatures) compared to larger capillaries. , Therefore, capillary size and distribution controls the whole process, meaning further phase change and the displacement and entrapment of the gas and liquid phases. In our prior studies, vaporization temperatures of various hydrocarbons were studied using different lab-scale capillary models such as Hele–Shaw silica-glass cells, microfluidics chips, and reservoir rocks (Berea sandstone, Indiana limestone, tight sandstone, and shale). These studies qualitatively and quantitively investigated the phase behavior (boiling temperatures and pressures of hydrocarbon solvents) and showed that phase change occurs more quickly as the medium becomes tighter.…”
Section: Introductionmentioning
confidence: 99%
“…Phase alteration is a commonly encountered phenomenon in many engineering applications and natural processes in underground reservoir systems or synthetic porous media. These include CO 2 sequestration, conventional and unconventional oil and gas production, geothermal systems, waste deposition, and synthetic porous systems such as filters. Throughout the primary production period of oil or gas, the decline of reservoir pressure leads to the vaporization of hydrocarbons, starting from the lighter components.…”
Section: Introductionmentioning
confidence: 99%
“…This was first formulated by Lord Kelvin (Thomson 1872) indicating that the saturation pressure and temperature are inversely proportional to the capillary size. This yields lower temperatures for boiling (Al-Kindi & Babadagli 2018, 2019b or lower pressures for condensation (Tsukahara et al 2012;Bao et al 2017;Zhong et al 2018; Al-Kindi & Babadagli 2019a) than those in bulk media. Thome (2004) studied the evaporation behaviour and two-phase flow in microchannels and provided experiments and theory related to the evaporation in confined channels.…”
Section: Introductionmentioning
confidence: 99%